2013
DOI: 10.3390/toxins5111965
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Mycotoxin Combinations Involving Ochratoxin A

Abstract: Ochratoxin A (OTA) is a nephrotoxic mycotoxin with carcinogenic properties. Its presence was detected in various foodstuffs all over the world but with significantly higher frequency and concentrations in areas with endemic nephropathy (EN). Even though food is often contaminated with more than one mycotoxin, earlier studies focused on the occurrence and toxicology of only OTA. Only a limited number of surveys showed that OTA co-occurs in food with mycotoxins (citrinin-CIT, penicilic acid, fumonisin B1-FB1, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 108 publications
(154 reference statements)
2
53
0
3
Order By: Relevance
“…Mycotoxin combinations can result in antagonistic, additive and synergistic effects depending on cell type, endpoint and applied dose (Klari c et al, 2013). Klari c et al (2012) reported a dose dependant synergistic interaction between OTA and CIT measuring apoptotic effect; however, the same treatment had an antagonist effect on micronucleus rate.…”
Section: Discussionmentioning
confidence: 96%
“…Mycotoxin combinations can result in antagonistic, additive and synergistic effects depending on cell type, endpoint and applied dose (Klari c et al, 2013). Klari c et al (2012) reported a dose dependant synergistic interaction between OTA and CIT measuring apoptotic effect; however, the same treatment had an antagonist effect on micronucleus rate.…”
Section: Discussionmentioning
confidence: 96%
“…Food contamination by CIT is usually observed together with contamination by other nephrotoxic mycotoxins, mainly with OTA. These two mycotoxins are considered to be the cause of endemic nephropathy [1,7,8]. In comparison with other mycotoxins, CIT contamination of food and food commodities is rather rare.…”
Section: Introductionmentioning
confidence: 98%
“…The two toxins together also increase degeneration in kidney proximal tubules (Klarić et al, 2013;Stoev, 2013;Stoev and Denev, 2013). The synergistic worm toxicity of penicilllic acid and ochratoxin A is interesting as the fungi producing these combinations of toxins are often growing in corn and other cereals (Lund and Frisvad, 1994;Visagie et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%